Coastal hydraulics modeling: model set up and data collection - Abd. Wahab, Ahmad Khairi (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1996)
The interaction of hydrodynamic forces in the coastal and estuarial areas is a complex phenomenon. It may however, be simulated using computer models. The use of numerical models helped in analysing and investigating hydrodynamic behaviour. This in tum facilitated the processes of design and decision making in coastal engineering design works. There are various types of computer model in use but for each application it is important to apply the correct model set-up to ensure optimum execution and reliable outputs. This paper introduces typical sample of such models with greater emphasis on tidal models. The practical aspects of setting up the model and data collection are presented. This is based on many years' experience of using and developing such models